2009
DOI: 10.1002/j.2161-0029.2009.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregivers: Psychosocial Impacts and Clinical Needs

Abstract: The authors describe how 3 groups of family caregivers (spouses, daughters, and sons)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
(78 reference statements)
0
13
0
1
Order By: Relevance
“…, Daire et al . ). It is also the key to breaking the repetitive violence and to forestall the eruption of violence (Nicholas & Rasmussen ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…, Daire et al . ). It is also the key to breaking the repetitive violence and to forestall the eruption of violence (Nicholas & Rasmussen ).…”
Section: Discussionmentioning
confidence: 97%
“…This is crucial for helping families cope by re-establishing equilibrium, and decreasing emotion-focused coping skills, such as denial and avoidance. This type of programme may be instrumental in allowing family caregivers to prevent violence (Paterson et al 2002, Daire et al 2009). It is also the key to breaking the repetitive violence and to forestall the eruption of violence (Nicholas & Rasmussen 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the negative psychological effects of caregiving, many caregivers report positive outcomes (Daire, Torres, & Edwards, ; Robison, Fortinsky, Kleppinger, Shugrue, & Porter, ). Caregivers who are well supported report higher levels of emotional satisfaction and positive well‐being (Otis‐Green & Juarez, ).…”
Section: The Processes Of Care: Fostering Resiliencementioning
confidence: 99%
“…Studies have shown that family demands decrease health for some, but not all, people (Artazcoz et al, 2004;Regidor et al 2010); and caregivers often neglect their own health needs because of high family demands (Daire, Torres, & Edwards, 2009). Studies have shown that family demands decrease health for some, but not all, people (Artazcoz et al, 2004;Regidor et al 2010); and caregivers often neglect their own health needs because of high family demands (Daire, Torres, & Edwards, 2009).…”
Section: Primary and Secondary Stressorsmentioning
confidence: 99%
“…Not surprisingly, with inconsistent measures of family demands, there is little consistency in the research findings. Studies have shown that family demands decrease health for some, but not all, people (Artazcoz et al, 2004;Regidor et al 2010); and caregivers often neglect their own health needs because of high family demands (Daire, Torres, & Edwards, 2009). No research was available on how subjective family demands influenced health.…”
Section: Provision Of Activities Of Daily Livingmentioning
confidence: 99%